Kandungan logam berat (Hg, Pb) dan histopatologi (insang, daging, hati, limpa) ikan selar tetengkek (Megalaspis cordyla L) di Teluk Palu - Paundanan, Matius -; Fajrah, Sitti; Rikwan, - (Environmental Science Program, Ivet University, 2020)
Background: Palu bay waters are susceptible to the heavy metals pollution due to the inclusion of the waste product of Palu city, agriculture waste, and traditional mining waste. At certain concentrations of heavy metal contamination of Hg and Pb in aquatic organisms can be toxic to the organisms. The objectives of this research was to determine the contamination of heavy metals mercury (Hg, and lead (Pb) and to analyze the histopathology of gill, meat, liver, and spleen torpedo scad fish. Methods: Hg and Pb contents in torpedo scad fish compared to SNI No. 7387: 2009 on Limit of Metal Contamination in Food Ingredients. Histopathological preparations were analyzed descriptively. Results: The results showed that Hg contents in gill, meat, liver, and spleen were 0,007-0,145 mg/kg; 0,014-0.046 mg/kg; 0,052-0,106 mg/kg, and 0,043-0,414 mg/kg, respectively. Pb contens in gill, meat, liver, and spleen were 0.132-0,775 mg/k; 0,005-0,734 mg/kg, 0,295-1,871 mg/kg, and 1,654-12,923 mg/kg, respectively. There were gill showed inflammation in secondary lamella; meat contained mineral deposits, and showed fatty degeneration and necrosis; liver contained mineral deposits and showed hepatocytes degeneration and necrosis; whils spleen contained mineral deposits and showed degeneration and depletion. Conclusions: The average of Hg and Pb contents in all observed fish organs were below of the quality standards, except for Pb concentrations in gill, liver, and spleen. Histopathological preparations were analyzed descriptively. Based on the histopathological analysis of fish organs, there were abnormality in each organ. KEY WORDS: heavy metals; histopathological; Megalaspis cordyla; Palu Bay